Empirical properties of diversion ratios. (8th December 2021) - Conlon, Christopher; Mortimer, Julie Holland
Abstract: The diversion ratio for products j and k is the fraction of consumers who leave product j after a price increase and switch to product k . Theoretically, it is expressed as the ratio of demand derivatives from a multi‐product firm's Bertrand‐Nash first‐order condition. In practice, diversion ratios are also measured from second‐choice data or customer‐switching surveys. We establish a LATE interpretation of diversion ratios, and show how diversion ratios are obtained from different interventions (price, quality, or assortment changes) and how those measures relate to one another and to underlying properties of demand.